Lessons for Policing from Moneyball: The Views of Police Managers – A Research Note - Vito, Anthony G. (American journal of criminal justice, 2013)
Michael Lewis’ book Moneyball demonstrates how Oakland A’s General Manager Billy Beane used research evidence to improve his team’s performance in a cost-effective manner. This presentation focuses upon the responses of police managers attending the Administrative Officer’s Course in the Southern Police Institute at the University of Louisville. The respondents identified three elements of Moneyball that could be applied to police management: 1) using statistical analysis to guide operations, 2) challenging the status quo, and 3) doing more with less.